1971
DOI: 10.1111/j.1365-2621.1971.tb06399.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Physical Changes in Carrots as Affected by Blanching, Cooking, Freezing, Freeze Drying and Compression

Abstract: SUMMARY— The effect of processing variables on the cell structure and physical characteristics of carrots were determined. The phloem portion of fresh carrots was subjected to one of the following treatments: blanching; cooking for 10 min; freezing at 0°F, −30°F or −320°F; freeze drying, compressing after freeze drying at approximately 1500 psi. Carrots at each treatment were tested for: (1) texture by means of the Ailo‐Kramer Shear Press; (2) water holding capacity by centrifuging at 500, 1000, 1500, 2000 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

1978
1978
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 5 publications
1
25
0
1
Order By: Relevance
“…The textural changes in carrots during blanching have been investigated by Fuchigami et al, 12 Glasscock et al 32 and Rahman et al 14 Glasscock et al 32 found higher shear values for carrots following microwave blanching than following water blanching after one month of frozen storage. The same tendency in the textural attributes was seen in the present study.…”
Section: Discussion and Conclusion Blanchingmentioning
confidence: 97%
“…The textural changes in carrots during blanching have been investigated by Fuchigami et al, 12 Glasscock et al 32 and Rahman et al 14 Glasscock et al 32 found higher shear values for carrots following microwave blanching than following water blanching after one month of frozen storage. The same tendency in the textural attributes was seen in the present study.…”
Section: Discussion and Conclusion Blanchingmentioning
confidence: 97%
“…The exudate increased at lower freezing rates, but not significantly. The freezing rate and the amount of juice exuded were inversely proportional to each other, as has been found to be the case for cranberries and wild blackberries [6], unblanched carrots [16], green beans and peas [17] and carrots [4]. Then again the amount of exudate proved to be directly proportional to thawing rate, highlighting the advantage of thawing slowly.…”
Section: Resultsmentioning
confidence: 85%
“…Heat treatment caused gross changes in the parenchyma tissue structure of the fruit (Fig 4D) as a result of changes in the chemical constitution of the middle lamella which affected its adhesive properties, 14,15 thus permitting cell separation to occur (Figs 4E and 4F). Examination of fracture surfaces showed that most cells remained intact, suggesting that tissue failure occurred by cellto-cell debonding and that the resulting decrease in ®rmness of olive fruit was related to the formation of soluble pectins.…”
Section: Resultsmentioning
confidence: 96%